Studi Pengolahan Limbah Cair Industri Tahu dengan Media Biofiltrasi Zeolit - Dedi Anwar; Disna Damayanti Wijaya; Ismadi Raharjo (Jurusan Teknologi Pertanian, 2015)
The liquid waste is waste that most potential to pollute the environment. Most of the liquid waste originating from separate viscous liquid of clots in the manufacturing process and the filtration is called whey. Other sources of liquid waste from the process of manufacturing know. The amount of liquid waste generated by industrial manufacturing know is comparable to the use of water for processing. This study aims to determine the effect of detention time, the percentage of sludge to the concentration of COD, pH, TDS, NH3 and H2S from industrial wastewater carried out in aquarium biofiltration media testers with zeolite. Variable research operation is 12 days with 10% sludge and 14 days with 20% sludge. The results of this study, that the detention time effect on the concentration of COD reduction, TDS, NH3, H2S and pH rise. More significant decline occurred during the time of stay of 14 days with the provision of sludge by 20% with a total decline of COD 45,5 mg/liter/day, the results are consistent effluent quality standard PP No. 82 of 2001 with a threshold of 50 ppm, and 59,8 mg TDS/liter day, and for the TDS of 1000 ppm. Handling after a stay in the aquarium is the process of aeration for 2 days and 5 days with aerator power of 2,5 liters/sec to lower concentrations of NH3 and H2S. From the analysis that has been done, the concentration of H2S after aeration diving 5 days, 525 mg/lt. Based on these results indicate reduction of H2S ineligible waste water effluent quality standards. While the concentration of NH3 qualify allocated for â€œwater class IIIâ€. NH3 concentration after aeration for 5 days is 0,2 ppm.Â Keywords: biofilters, zeolite, detention time